Context and the attitudes - Richard, Mark. (Oxford : Oxford University Press, 2013)
Thirteen seminal essays by Mark Richard develop a nuanced account of semantics and propositional attitudes. The collection addresses a range of topics in philosophical semantics and philosophy of mind, and is accompanied by a new Introduction which discusses attitudes realized by dispositions and other non-linguistic cognitive structures.
Introduction : mental states and their ascription -- Direct reference and ascriptions of belief -- Quantification and Leibniz's law -- Attitude ascriptions, semantic theory, and pragmatic evidence -- How I say what you think -- Attitudes in context -- Defective contexts, accommodation, and normalization -- Propositional quantification -- Sense, necessity, and belief -- Semantic pretense -- Intensional transitives and empty terms -- Objects of relief -- Meaning and attitude ascriptions -- Kripke's puzzle.
Includes bibliographical references (p. [283]-285) and index.
Keywords: Semantics (Philosophy); Propositional attitudes